G218(P) A new sepsis tool: improving the management of children with suspected sepsis in our emergency department, with an unexpected bonus. (25th October 2020) - Clubb, R; Dakova, A; Anpananthar, A
Abstract : Aim: Sepsis is a leading cause of morbidity and mortality in children. Early recognition and appropriate management can save lives. With on-going staff cover challenges in our busy District General Hospital we wanted to implement sustainable changes to improve early recognition and prompt senior review and delivery of antibiotics to potentially septic children in the Emergency Department. Method: Following focus groups with key stakeholders and the multidisciplinary team (MDT), a sepsis triage tool based on the Wessex Paediatric Sepsis Tool was introduced to enable nurses to screen all children presenting with 'illnesses'. Retrospective analysis of ED data was performed before and after implementation. Three mini PDSA cycles helped us improve the tool, increase the MDT's engagement and make its continued use sustainable. Results: Focus groups suggested that the ED team found the tool easy to use and that it resulted in early review of children identified as potentially septic. Promptly amending the tool in response to feedback anecdotally helped keep staff engaged. The pre-implementation audit undertaken in January 2019 screened 368 children who presented to the ED with an illness. Post-implementation, 300 children were screened. The time from arrival to a senior being notified of a potentially septic child who met the criteria for triggering the tool improved from 53 minutes to 19 minutes, while the time to senior review decreased to 2 hours 17 minutes, from 4 hours 29 minutes. Senior review of potentially septic children increased from 50% to 85%. Conclusion: We achieved improvements in key times in the patient's journey, which could lead to improvement in patient flow in paediatric ED and reduced time to antibiotics. Implementation of this tool also encouraged regular education sessions on sepsis for the MDT. Importantly, staff feedback though PDSA cycles has also opened other doors. It led to the conversion of two ED cubicles into paediatric critical care bays to facilitate rapid senior review, shorten the time taken to give antibiotics and improve patient flow in ED for other critically unwell children.